Magnetic demercuration adsorbent applied to water-containing flue gas and preparation method of magnetic demercuration adsorbent

By preparing a magnetic copper slag-based adsorbent, a porous structure is formed by using the chelation and complexation reaction of sodium alginate and copper nitrate, the problem of low removal efficiency of elemental mercury in aqueous glow gas is solved, and magnetic separation of the adsorbent and efficient recovery of valuable metals are achieved.

CN119771354APending Publication Date: 2025-04-08SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510133865.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove elemental mercury in water-containing gas, and the recycling process of valuable metals is complex and the recovery rate is low, making it difficult to purify individual metals.

Method used

A magnetic demercury adsorbent is prepared by using copper slag, and chelating and complexing reactions with sodium alginate and copper nitrate solutions to form a magnetic adsorbent, and a porous structure is formed by pyrolysis treatment.

Benefits of technology

It has achieved efficient adsorption of elemental mercury in aqueous flue gas, with a demercury rate of up to 95%, and the recycling of adsorbents is realized through magnetic separation, improving the recycling efficiency of valuable metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771354A_ABST
    Figure CN119771354A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic demercuration adsorbent applied to water-containing flue gas and a preparation method, and belongs to the technical field of flue gas purification. The preparation method comprises the following steps: firstly, carrying out pretreatment and magnetic separation on the copper slag, grinding the copper slag into particles, adding the particles into a sodium alginate solution, and fully stirring; then titrating the solution obtained after stirring into a copper nitrate solution, and freeze-drying the obtained rubber balls in a vacuum freeze-drying machine; and putting the sample obtained by freeze drying into a fixed bed for pyrolysis, and cooling after the pyrolysis is finished, thereby obtaining the product. The solid waste copper slag is used as a raw material, and solid waste disposal and metal extraction and reutilization are achieved; and the energy consumption is low in the preparation process of the magnetic mercury removal adsorbent. Meanwhile, the prepared magnetic mercury removal adsorbent can better realize mutual combination of metal iron and a carbon material, has water resistance, and can realize high mercury adsorption efficiency in water-containing flue gas, and the real-time mercury removal efficiency can reach 95% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flue gas purification, and particularly relates to a magnetic mercury removal adsorbent and a preparation method thereof. Background Art

[0002] The proportion of elemental mercury in fixed combustion flue gas is about 24%, and the proportion of elemental mercury in the exhaust flue gas is relatively high, causing serious harm to the environment and human health. Elemental mercury is volatile, difficult to dissolve in water, and can be transmitted over long distances, which is a difficulty in mercury removal. The existing mercury removal technologies mainly include ultra-low emissions, coordinated emissions, and single mercury removal. Among them, the adsorbent injection method in single mercury removal is a very promising technology that can be applied to occasions that do not meet the requirements for elemental mercury emissions. Adsorbent injection can achieve efficient adsorption of elemental mercury, and can use existing dust removal equipment to achieve subsequent adsorbent collection and heavy metal mercury recovery.

[0003] Pyrometallurgical copper smelting is the main process for producing copper, and copper slag is a by-product of this process. When smelting 1 ton of refined copper, 2.2 tons of copper slag are produced. If copper slag is treated by simple solid waste treatment methods such as stacking, it will cause serious water pollution and soil pollution. As an excellent inorganic material, copper slag itself contains a large amount of recyclable valuable metals. One of the notable characteristics of this slag is that it is rich in valuable metals such as iron, copper and cobalt. It mainly contains Fe2O3, SiO2, CaO, Al2O3 and CuO. However, the corresponding difficulty is that the recovery process of valuable metals is difficult, the recovery rate is low, and iron and copper are more difficult to separate, making it difficult to purify a single metal. Therefore, in terms of copper slag treatment, if the value of copper slag itself can be utilized, copper slag pretreatment and iron screening can be carried out and utilized, and the strategy of "using waste to treat poison" can be adopted, it can not only realize the resource reuse of copper slag, but also solve the pollution problem caused by elemental mercury, and also make the obtained adsorbent have a certain magnetism, so as to realize the recycling of adsorbent.

[0004] Metal-based adsorbents for mercury removal have high reaction efficiency, but their sample specific surface area is small; although carbon-based adsorbents have large specific surface area and high adsorption rate, their adsorption efficiency is relatively poor. In addition, both have the problem of water resistance to be improved during the mercury removal process. Therefore, the special structure of carbon-based carriers can be used to give play to their huge specific surface area and pore structure advantages to achieve the number and dispersion of active site loading of metal oxides on the carbon surface, which is very potential. However, a certain amount of metal loading can be achieved by using impregnation method, ultrasonic co-precipitation method, in-situ polymerization method, etc., but the loading amount and metal dispersion cannot be guaranteed, and the water resistance is not ideal.

[0005] The adsorbent used in water-containing flue gas is different from conventional adsorbents. It needs to have good water resistance so as not to be affected by water vapor. The iron-based catalysts in the prior art are very susceptible to the obstruction of water in the flue gas during the removal of elemental mercury. In addition, the pore size distribution of metal materials such as iron-based adsorbents is generally not conducive to the adsorption of elemental mercury. Therefore, it can be seen that the research of a magnetic adsorbent suitable for water-containing flue gas and with high mercury removal efficiency is a difficult problem that researchers in this field urgently need to solve. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, which can not only recycle copper slag resources, but also achieve efficient mercury adsorption efficiency in water-containing flue gas, and the real-time mercury removal efficiency can reach more than 95%.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, the method comprising the following steps:

[0009] a. Pre-treating the copper slag and grinding it into particles;

[0010] b. Prepare 1 wt% sodium alginate solution and copper nitrate solution respectively;

[0011] c. adding the copper slag ground in step a to the sodium alginate solution to achieve chelation between the functional groups in the sodium alginate and the metals in the ground copper slag to obtain a mixed solution; the mass volume ratio of the ground copper slag to the sodium alginate solution is 1:0.1 g / L;

[0012] d. dropping the mixed solution into a copper nitrate solution to cause a complex reaction to obtain a rubber ball;

[0013] e. freeze-drying the gel balls to obtain a sample in a solid form;

[0014] f. Place the sample in a fixed bed for pyrolysis at a temperature of 500 to 750° C. for a pyrolysis time of 0.5 to 2 h. During the pyrolysis, introduce nitrogen at a certain flow rate as a protective gas to obtain the product.

[0015] The beneficial technical effects directly brought about by the above technical solution are:

[0016] Step a can perform simple and convenient screening and treatment of the copper slag sample, and use the magnetism of iron oxide to screen out the target metal, so as to facilitate the efficient application of the copper slag; step c can realize the chelation of the functional groups in the sodium alginate and the metal in the copper slag, and provide structural support for the dispersion of the metal; step d can react the mixed solution with the copper nitrate solution to realize the complex reaction of the two; step e can dehydrate the rubber balls to realize drying and form a carrier with a transparent pore structure; step f can carbonize the sample to realize a porous structure of micropores, mesopores and macropores.

[0017] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step a, the step of pretreating the copper slag is: performing magnetic separation on the copper slag three times, grinding the obtained copper slag into particles with a particle size of 220 meshes, and obtaining ground copper slag.

[0018] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step b, sodium alginate is dissolved in water to obtain a 1wt% sodium alginate solution; copper nitrate is dissolved in water to obtain a 1wt% copper nitrate solution.

[0019] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step c, the ground copper slag is added to the sodium alginate solution for a chelating time of 3 to 5 hours.

[0020] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step d, the mixed solution is loaded into a separatory funnel and titrated into a 0.4L copper nitrate solution to undergo a complex reaction, wherein the temperature of the copper nitrate solution is 25-35°C.

[0021] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step e, freeze drying is performed in a freeze dryer, and the freeze drying time is 20 to 25 hours.

[0022] In the above-mentioned method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, in step f, the gas flow rate of nitrogen is 0.5 to 1.5 L / min.

[0023] The above-mentioned preparation method of the magnetic demercuration adsorbent for use in water-containing flue gas, the application steps of the magnetic demercuration adsorbent are: placing the magnetic demercuration adsorbent in a tubular furnace, the initial inlet elemental mercury concentration of the tubular furnace is 50μg / m 3 The reaction temperature of the tube furnace is 20-180° C., the relative humidity is 5%, and the outlet tail gas is introduced into an automatic mercury meter, which measures and records the real-time concentration of elemental mercury at the outlet of the tube furnace.

[0024] Another object of the present invention is to provide the above-mentioned magnetic mercury removal adsorbent for use in water-containing flue gas, which is prepared by the above-mentioned preparation method, and the magnetic mercury removal adsorbent is in a black powder state.

[0025] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0026] (1) The present invention utilizes copper smelting waste slag as raw material, thereby realizing the recycling of the waste slag, and can be roughly screened using magnets, thereby greatly reducing processing energy consumption.

[0027] (2) The magnetic demercuration adsorbent prepared by the present invention successfully combines metal elements with carbon sources, and compared with the traditional carbon material impregnation treatment, the achieved metal dispersion is very excellent.

[0028] (3) The magnetic mercury removal adsorbent prepared by the present invention can also adsorb elemental mercury, and the mercury removal rate can reach 95%. Moreover, the removal efficiency rate can also reach 95% when there is water in the flue gas, and has a certain water resistance.

[0029] (4) The magnetic mercury removal adsorbent prepared by the present invention has magnetism. Due to the doping of copper slag, the iron oxide in the copper slag is successfully loaded into the adsorbent during the preparation process, and it also has magnetism, so that after the adsorbent is sprayed into the flue gas duct to play a role, it can be magnetically separated in the subsequent fly ash slag. The separated adsorbent can be centrally heated, and the released elemental mercury can be uniformly collected and cooled, thereby achieving effective removal and effective collection of heavy metal mercury.

[0030] (5) The magnetic demercuration adsorbent prepared by the present invention can achieve an effective combination of carbon materials and metal materials. Compared with the traditional carbon material impregnation treatment, the adsorbent obtained by this method can achieve a higher metal loading capacity and a more transparent structure.

[0031] In summary, the magnetic demercuration adsorbent prepared by the present invention can achieve the loading and deposition of copper slag components, and can obtain a structure with relatively rich pore sizes, thereby achieving high efficiency in capturing gaseous elemental mercury; and in the case of water in the flue gas, the adsorbent can also achieve good water resistance and will not be affected by water vapor. The magnetic demercuration adsorbent of the present invention has high efficiency in removing elemental mercury, and the preparation method is simple and easy to operate, which is convenient for magnetic separation and mercury collection. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings:

[0033] Figure 1 This is the HRTEM image of the magnetic mercury removal adsorbent of Example 1 of the present invention.

[0034] Figure 2This is a graph showing the mercury removal efficiency of the magnetic mercury removal adsorbent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application.

[0036] The raw materials described in the present invention can be purchased through commercial channels.

[0037] In the present invention, the pretreatment step of the copper slag is: the copper slag obtained from the smelter is subjected to magnetic separation, and the sample after separation three times is ground and screened. For example, the present invention preferably selects a 220-mesh copper slag sample.

[0038] The main technical concept of the present invention is: in the previous research, the focus was on the research of magnetic adsorbents for mercury removal, and the removal effect of iron-based adsorbents on elemental mercury was verified. However, the pore size distribution of metal materials such as iron-based adsorbents is generally not conducive to the adsorption of elemental mercury, and it is very susceptible to the obstruction of moisture in the flue gas. Unlike adsorbents prepared by others, the magnetic demercuration adsorbent of the present invention utilizes components such as iron oxide in waste copper slag for the removal of elemental mercury. The present invention focuses on the method of integrating iron-based and carbon-based materials, combining the advantages of both. The carbon-based material has a relatively rich pore structure, which is conducive to the occurrence and progress of chemical reactions. At the same time, the prepared iron-carbon adsorbent itself contains more functional groups and defect sites, which also helps to remove elemental mercury; finally, the preparation method of the present invention can solve the problem of metal extraction and disposal of waste copper slag, and can achieve effective metal recycling in copper slag under the premise of low energy consumption.

[0039] Embodiment 1:

[0040] The present invention provides a method for preparing a magnetic mercury removal adsorbent, which specifically comprises the following steps:

[0041] The first step is to separate the obtained copper slag three times with a magnet and grind it into 220 mesh particles.

[0042] The second step is to dissolve sodium alginate in water to prepare a 1 wt% sodium alginate solution; and to dissolve copper nitrate in water to prepare a 1 wt% copper nitrate solution of the sodium alginate solution.

[0043] Step 3: Weigh 4 g of the copper slag ground in the first step and add it to 0.4 L of 1 wt% sodium alginate solution with the optimal concentration, and stir it magnetically;

[0044] Step 4: After 4 hours of magnetic stirring, the mixture was added dropwise into 0.4 L of 1 wt% copper nitrate solution at 30°C to produce a complexation reaction to obtain rubber balls.

[0045] Step 5: freeze-dry the obtained rubber balls in a vacuum freeze dryer for 24 hours to obtain a sample;

[0046] Step 6: Place the sample in a fixed bed and set the pyrolysis temperature to 700°C for 0.5 h, during which nitrogen protective gas is introduced at a flow rate of 1 L / min. After the pyrolysis is completed, a magnetic demercuration adsorbent is obtained.

[0047] In the magnetic demercuration adsorbent of this embodiment, the copper slag added in the third step will be successfully loaded into the adsorbent to become active metallic iron oxide, and the magnetic adsorbent obtained by freeze drying in the fifth step will be evenly distributed in the adsorbent without agglomeration and other problems.

[0048] The magnetic adsorbent prepared in this example was used to remove elemental mercury, and the specific steps were as follows:

[0049] Finally, the obtained magnetic demercuration adsorbent was used to remove elemental mercury. The main equipment used in the demercuration experiment was a tube furnace, and the following parameters were set:

[0050] The initial inlet elemental mercury concentration of the tube furnace is 50 μg / m 3 , the reaction temperature is 80℃, the relative humidity is 5%, and the outlet tail gas is passed into an automatic mercury meter to measure and record the real-time concentration of elemental mercury at the outlet of the tube furnace. After the sample is demercured, the concentration of elemental mercury drops to 0μg / m 3 The removal efficiency of elemental mercury in 1 hour of reaction is 95%. In addition, the obtained magnetic demercuration adsorbent has magnetic properties before and after the reaction, which makes the injection application of the magnetic demercuration adsorbent feasible.

[0051] The HRTEM image of the magnetic mercury removal adsorbent of this embodiment is as follows: Figure 1 As shown, the mercury removal efficiency of the magnetic mercury removal adsorbent of this embodiment is shown in FIG. Figure 2 shown.

[0052] Embodiment 2:

[0053] The difference from Example 1 is that:

[0054] The pyrolysis temperature in the sixth step is 650°C.

[0055] The magnetic mercury removal adsorbent prepared in this example was subjected to a mercury removal experiment, and the specific steps were the same as those in Example 1. After 1 hour of reaction, the removal efficiency of elemental mercury reached 95%, and the obtained magnetic mercury removal adsorbent had magnetism before and after the reaction.

[0056] Embodiment 3:

[0057] The difference from Example 1 is that:

[0058] The pyrolysis temperature in the sixth step is 750°C.

[0059] The magnetic mercury removal adsorbent prepared in this example was subjected to a mercury removal experiment, and the specific steps were the same as those in Example 1. After 1 hour of reaction, the removal efficiency of elemental mercury reached 90%, and the obtained magnetic mercury removal adsorbent had magnetism before and after the reaction.

[0060] Embodiment 4:

[0061] The difference from Example 1 is that:

[0062] The reaction temperature in the tube furnace is 140°C. After 1 hour of reaction, the removal efficiency of elemental mercury reaches 90%. The obtained magnetic mercury removal adsorbent has magnetic properties before and after the reaction.

[0063] Embodiment 5:

[0064] The difference from Example 1 is that:

[0065] Step 4: During the titration process, the temperature of the copper nitrate solution is 35°C.

[0066] The magnetic mercury removal adsorbent prepared in this example was used to carry out a mercury removal experiment, and the specific steps were the same as those in Example 1.

[0067] Comparative Example 1:

[0068] The copper slag directly collected from the smelting of copper concentrate was used as a catalyst and placed in simulated flue gas. The catalytic performance of elemental mercury was characterized at a reaction temperature of 200-300°C. It was found that the oxidation efficiency of elemental mercury was 93.8% at 250°C. The feasibility of copper slag as an oxidation catalyst was revealed. The simulated flue gas mainly used HCl and O2, and there was no mention of resistance to water vapor in the flue gas; and the temperature used for the catalyst was 200-300°C, which is suitable for SCR denitrification devices and has nothing to do with the application of dust collector equipment at around 120°C.

[0069] Comparative Example 2:

[0070] Copper slag-based porous geopolymer spheres were obtained at room temperature using copper slag powder and foaming agents. This method achieved low-temperature solidification, waste recycling, and adsorption of heavy metal ions in wastewater. There was no mention of the combined loading method of copper slag and carbon materials, the construction of microstructures, and the removal of gaseous pollutants.

[0071] Comparative Example 3:

[0072] Fe-C adsorbents are prepared by ultrasound, and the cumulative mercury removal efficiency in a fixed bed over a period of time reaches about 93%, but it is easily inhibited by the influence of other components of flue gas. The preparation method of the adsorbent of the present invention is different from the impregnation method. Instead, it uses the chelation reaction of metal and alginate for loading. The loaded metal has better dispersion, and there will be no problems such as metal loading agglomeration and low effective loading.

[0073] Comparative Example 4:

[0074] The composite material was prepared by using copper slag and polyaniline by ultrasonic dispersion. The copper slag was used as the core and the polyaniline was used as the shell to adsorb heavy metal ions in water. The focus of the preparation of this adsorbent is to screen and utilize the metal in the copper slag and to achieve an adsorbent that combines metallic iron with carbon materials, with high dispersion of the loaded metal and hydrophobic properties.

[0075] Comparative Example 5:

[0076] The first step is to separate the obtained copper slag three times with a magnet and grind it into 220 mesh particles.

[0077] The second step is to dissolve sodium alginate in water to prepare a 1 wt% sodium alginate solution; and to dissolve copper nitrate in water to prepare a 1 wt% copper nitrate solution of the sodium alginate solution.

[0078] Step 3: Weigh 4 g of the copper slag ground in the first step and add it to 0.4 L of 1 wt% sodium alginate solution with the optimal concentration, and stir it magnetically;

[0079] Step 4: After 4 hours of magnetic stirring, 0.4 L of 1 wt% copper nitrate solution was dripped into the mixed solution obtained in step 3 to cause a complexation reaction to obtain rubber balls;

[0080] Step 5: freeze-dry the obtained rubber balls in a vacuum freeze dryer for 24 hours to obtain a sample;

[0081] Step 6: Place the sample in a fixed bed and set the pyrolysis temperature to 700°C for 0.5 h, during which nitrogen protective gas is introduced at a flow rate of 1 L / min. After the pyrolysis is completed, a magnetic demercuration adsorbent is obtained.

[0082] The mercury removal efficiency of the magnetic mercury removal adsorbent prepared in this comparative example is only 70%.

[0083] In summary, the magnetic mercury removal adsorbent of the present invention uses copper slag as the main raw material. By improving the preparation method, the obtained magnetic mercury removal adsorbent can achieve efficient mercury removal and can fully utilize the solid waste copper slag.

[0084] Parts not described in the present invention can be implemented by referring to the existing technology.

[0085] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present application and are not intended to be limiting of the present application. As long as they are within the spirit of the present application, appropriate changes and modifications to the above embodiments should fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas, characterized in that: The preparation method comprises the following steps: a. Pre-treating the copper slag and grinding it into particles; b. Prepare 1 wt% sodium alginate solution and copper nitrate solution respectively; c. adding the copper slag ground in step a to the sodium alginate solution to achieve chelation between the functional groups in the sodium alginate and the metals in the ground copper slag to obtain a mixed solution; the mass volume ratio of the ground copper slag to the sodium alginate solution is 1:0.1 g / L; d. dropping the mixed solution into a copper nitrate solution to cause a complex reaction to obtain a rubber ball; e. freeze-drying the gel balls to obtain a sample in a solid form; f. Place the sample in a fixed bed for pyrolysis at a temperature of 500 to 750° C. for a pyrolysis time of 0.5 to 2 h. During the pyrolysis, introduce nitrogen at a certain flow rate as a protective gas to obtain the product.

2. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step a, the step of pretreating the copper slag is: performing magnetic separation on the copper slag three times, grinding the obtained copper slag into particles with a particle size of 220 mesh, and obtaining ground copper slag.

3. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step b, sodium alginate is dissolved in water to obtain a 1wt% sodium alginate solution; copper nitrate is dissolved in water to obtain a 1wt% copper nitrate solution.

4. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step c, the ground copper slag is added to the sodium alginate solution for a chelating time of 3 to 5 hours.

5. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step d, the mixed solution is placed in a separatory funnel and titrated into a 0.4 L copper nitrate solution to undergo a complex reaction, wherein the temperature of the copper nitrate solution is 25-35° C.

6. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step e, freeze drying is carried out in a freeze dryer, and the freeze drying time is 20 to 25 hours.

7. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: In step f, the nitrogen gas flow rate is 0.5-1.5 L / min; the pyrolysis temperature is 650-700°C.

8. The method for preparing a magnetic mercury removal adsorbent for use in water-containing flue gas according to claim 1, characterized in that: The application steps of the magnetic demercuration adsorbent are as follows: placing the magnetic demercuration adsorbent in a tube furnace, wherein the initial inlet elemental mercury concentration of the tube furnace is 50 μg / m 3 The reaction temperature of the tube furnace is 20-180° C., the relative humidity is 5%, and the outlet tail gas is introduced into an automatic mercury meter, which measures and records the real-time concentration of elemental mercury at the outlet of the tube furnace.

9. A magnetic mercury removal adsorbent used in water-containing flue gas, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8, and the magnetic mercury removal adsorbent is in a black powder state.